2021
DOI: 10.3390/catal11121454
|View full text |Cite
|
Sign up to set email alerts
|

Floating Carbon-Doped TiO2 Photocatalyst with Metallic Underlayers Investigation for Polluted Water Treatment under Visible-Light Irradiation

Abstract: In the current study, we analysed the influence of metallic underlayers on carbon-doped TiO2 films for RhB decomposition and Salmonella typhimurium inactivation under visible-light irradiation. All the experiments were divided into two parts. First, layered M/C-doped-TiO2 film structures (M = Ni, Nb, Cu) were prepared by magnetron sputtering technique on borosilicate glass substrates in the two-step deposition process. The influence of metal underlayer on the formation of the carbon-doped TiO2 films was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 104 publications
(160 reference statements)
0
5
0
Order By: Relevance
“…Prior to the ZnO deposition, the HDPE beads were precovered with a thin layer of Ni (thickness of about 100 nm) using magnetron with Ni target (purity 99.99%, Kurt J. Lesker Company, Clairton, PA, USA) powered by a direct current power source. Our previous study disclosed that metallic underlayers can have positive impacts on the bactericidal effect of the photocatalyst under visible-light irradiation [28]. During the process, HDPE beads were placed under the unbalanced magnetron with a circular Zn target (99.99% purity and 76 mm diameter, Kurt J. Lesker Company, Clairton, PA, USA) which was powered by an RF power source working at 150 W for 1 h. After that, the HDPE beads were flipped over, and ZnO film was deposited on the other side of the beads under the same conditions.…”
Section: Zno Film Deposition On the Floating Substratementioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the ZnO deposition, the HDPE beads were precovered with a thin layer of Ni (thickness of about 100 nm) using magnetron with Ni target (purity 99.99%, Kurt J. Lesker Company, Clairton, PA, USA) powered by a direct current power source. Our previous study disclosed that metallic underlayers can have positive impacts on the bactericidal effect of the photocatalyst under visible-light irradiation [28]. During the process, HDPE beads were placed under the unbalanced magnetron with a circular Zn target (99.99% purity and 76 mm diameter, Kurt J. Lesker Company, Clairton, PA, USA) which was powered by an RF power source working at 150 W for 1 h. After that, the HDPE beads were flipped over, and ZnO film was deposited on the other side of the beads under the same conditions.…”
Section: Zno Film Deposition On the Floating Substratementioning
confidence: 99%
“…Meanwhile, some authors suggest that doping or other types of Ni and ZnO combination can be a suitable way to improve ZnO characteristics [24][25][26][27]. Moreover, our previous study revealed that Ni underlayer improves TiO 2 photocatalytic efficiency, which was applied as floating photocatalyst for Salmonella typhimurium inactivation under visible-light irradiation [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sol-gel step is applied and the intermediate is calcined at comparably moderate temperatures between 400 • C and 500 • C. [21][22][23] Beside the well-established methods, alternatives are tested such as high-energy grinding of anatase in ethanol and subsequent calcination at 200 • C. [24] To address the problem of catalyst recovery new methods were applied recently aiming at the synthesis of TiO 2 combined with magnetic metals. Magnetron sputtering is applied to fabricate films of carbon-doped anatase with underlying nickel [25] or bi-layered particles. [26] Theoretical calculations regarding the influence of pblock elements on the optical absorption are thoroughly reviewed by Di Valentin et al [27,28] Several other sources as well as experimental results showing the influence of p-block elements are for instance reviewed in the publication of Dozzi et al [10] The influence of carbon on the band gap of TiO 2 is thoroughly discussed for both theoretical calculations and experimental work.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] To address the problem of catalyst recovery new methods were applied recently aiming at the synthesis of TiO 2 combined with magnetic metals. Magnetron sputtering is applied to fabricate films of carbon‐doped anatase with underlying nickel [ 25 ] or bi‐layered particles. [ 26 ]…”
Section: Introductionmentioning
confidence: 99%